How Filipino is Filipino ; SOT Balik loob ; Miss Saigon II [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Filipino as a national language is booed and applauded by its detractors and its advocates. Look into the operation of the Special Operations Teams, its philosophy and effectivity as a way of changing the image of the aFP. Showcase the talents of Miss Saigon and their farewell concert at CCP.
How Filipino is Filipino (15 min.) -- SOT : Balik loob (22 min.) -- Miss Saigon II (18 min.)
VHS.
Keywords: Armed Forces of the Philippines; Filipino language; Philippine language